2007
DOI: 10.1080/10241220701387872
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and structure of hypervalent boron (10-B-5) compounds bearing a 2,6-(p-tolyloxymethyl)benzene tridentate ligand

Abstract: Several organoboron compounds having a tridentate ligand based on 2,6-bis(p-tolyloxymethyl)benzene (5) were prepared. X-ray crystallography revealed that the distances between the central boron and both oxygen atoms of the tridentate ligand varied from 2.50 Å to 3.16 Å . The boron atom of the pinacolato derivative (5a) was found to be tricoordinated, whereas those of the diphenyl (5b) and the catecholato derivative (5c) were pentacoordinated, although these molecular structures were unsymmetrical. Compound 5c … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 16 publications
0
6
0
Order By: Relevance
“…Since the former smaller basis set seemed to be sufficient for obtaining structural parameters similar to those for the X-ray structure, we decided to use it for further computations. Furthermore, the B3PW91 functional has been found to be more superior to the B3LYP functional for reproducing structural parameters of X-ray structures for analogous hypervalent carbon and boron compounds bearing neutral oxygen donors at the apical positions with only a slight overestimation of the bond lengths (deviation: 0.1% to 1.2%). , Thus, this functional was adopted in a combination with the 6-31G(d) basis set. Selected structural parameters of the two states deduced with the B3PW91/6-31G(d) method are shown in Table alongside the experimental data.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Since the former smaller basis set seemed to be sufficient for obtaining structural parameters similar to those for the X-ray structure, we decided to use it for further computations. Furthermore, the B3PW91 functional has been found to be more superior to the B3LYP functional for reproducing structural parameters of X-ray structures for analogous hypervalent carbon and boron compounds bearing neutral oxygen donors at the apical positions with only a slight overestimation of the bond lengths (deviation: 0.1% to 1.2%). , Thus, this functional was adopted in a combination with the 6-31G(d) basis set. Selected structural parameters of the two states deduced with the B3PW91/6-31G(d) method are shown in Table alongside the experimental data.…”
Section: Resultsmentioning
confidence: 99%
“…Since the capability to form short hypervalent bonds would require the apical donor groups to be attached to a more flexible backbone, carbon compounds 3 and boron compounds 4 using a van Koten-type tridentate ligand with oxygen donor sites were examined (Figure ) . X-ray electron-density analyses and DFT calculations suggested that these compounds ( 3 and 4 ) were also hypervalent compounds.…”
Section: Introductionmentioning
confidence: 99%
“…However, by deployment of the sterically rigid 1,8-dimethoxy-9-anthracenyl ligand framework (Chart , C ), Akiba and co-workers have successfully prepared, and structurally characterized, a raft of pentacoordinate boron compounds. The geometry about the central boron atom in each case is a result of a variety of factors including the inflexible ligand backbone, the pendant donor atoms in the 1 and 8 positions, and the nature of the substituents at the boron atom.…”
Section: Introductionmentioning
confidence: 99%
“…The geometries and relative stabilities of the singlet and triplet states of 8a (A = S) and 8b (A = NMe) were calculated at the B3PW91/6‐31G(d) level . The triplet states ( 8a T and 8b T , respectively) were found to be favored over the corresponding closed‐shell singlet states ( 8a CS and 8b CS , respectively) for both compounds (Δ E ST = E CS − E T = 12.6 and 14.0 kcal/mol for 8a and 8b , respectively).…”
Section: Resultsmentioning
confidence: 99%